Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

Mastering Derivatives

Download as pdf or txt
Download as pdf or txt
You are on page 1of 2

Quotient Rule

Divide each term of the numerator by the denominator before differentiating. Compare this with the
result you get by using the quotient rule:

𝑥+6 𝑥3 − 1 3𝑥 − 1
1. 2. 3.
𝑥 𝑥2 𝑥2
𝑥 3 − 3𝑥2 𝑥 4 + 2𝑥 3 2𝑥2 + 5𝑥 − 1
4. 5. 6.
𝑥 𝑥2 𝑥

Using negative indices, differentiate by using the product rule. Compare this with the result you get
by using the quotient rule:
𝑥+5 𝑥−3 3𝑥 + 8
7. 8. 9.
2𝑥 + 1 5𝑥 + 2 𝑥−5
𝑥2 − 2 𝑥3 𝑥+1
10. 11. 12.
𝑥2 + 9 𝑥+4 3𝑥2 − 7

Differentiate mentally without simplification (check your answers on the following page):
1 𝑥3 𝑥+4
13. 14. 15.
2𝑥 − 1 𝑥2 − 4 𝑥−6
2𝑥 + 5 𝑥 𝑥−7
16. 17. 2 18.
4𝑥 − 3 2𝑥 − 8 𝑥2
𝑥2 + 4𝑥 − 1 𝑥2 − 9𝑥 + 11 3𝑥 − 1
19. 20. 21.
𝑥+3 2𝑥 + 5 𝑥2 + 12
6𝑥 + 7 𝑥3 + 𝑥 5𝑥2 − 2𝑥
22. 2
23. 24.
𝑥 −𝑥+3 𝑥2 − 𝑥 − 1 3𝑥 + 1

Differentiate (using an embedded chain rule):


2𝑥 (2𝑥 + 7)3 𝑥−1
25. 1 26. 27.
(𝑥 + 1)2 4𝑥 − 1 (7𝑥 + 3)4

(3𝑥 − 4)5 2𝑥 − 5 √𝑥 − 1
28. 29. 30.
(2𝑥 + 1)3 √𝑥 + 1 4𝑥 + 1
√𝑥2 + 1 𝑥−4 (𝑥 + 3)4
31. 32. 3 33.
(𝑥 − 8)2 √𝑥 𝑥2

Find the derivative of:


2
𝑥+3 𝑝3
3
√𝑤
34. 𝑦= 35. 𝑓= 36. 𝑏=
√𝑥 + 2 2𝑝 + 1 𝑤2 +5
ℎ3 − 1 7𝑡 4 + 11 4𝑦 + 3 3
37. 𝑚= 38. 𝑔= 39. 𝑒=( )
ℎ3 + 1 𝑡+8 5𝑦 − 1

8𝑛2 − 5𝑛 + 11 𝑣−6 4𝑎 − 9
40. 𝑘= 41. 𝑟= 42. 𝑧= 3
𝑛+2 √(𝑣 + 1)5 (𝑎 + 5)4

Find the equation of the tangent to the following curves at the point indicated):
𝑥+3 𝑥+3 𝑥
43. 𝑦 = 𝑥−1 (2,5) 44. 𝑦 = 3𝑥−2 (1,4) 45. 𝑦 = 𝑥−2 (3,3)
𝑥2 𝑥2 +1 𝑥−7
46. 𝑦= (-1,-½) 47. 𝑦= (2,5) 48. 𝑦= 𝑥2
(1,-6)
𝑥−1 𝑥2 −3

http://www.CrystalClearMaths.com © Graeme Henderson (2015) ~ Free Use Permitted


~ Page 11 ~
Quotient Rule (Answers)
You should discover that the results are the same and that it is advisable to simplify expressions first!

6 𝑥3 + 2 2 3𝑥 − 2
1. − 2. =1+ 3. −
𝑥2 𝑥3 𝑥3 𝑥3
2𝑥2 + 1 1
4. 2𝑥 − 3 5. 2𝑥 + 2 6. =2+
𝑥2 𝑥2
You should discover that the results are the same and that the quotient rule is (usually) simpler to use.
9 17 23
7. − 8. 9. −
(2𝑥 + 1)2 (5𝑥 + 2)2 (𝑥 − 5)2
22𝑥 2𝑥 2 (𝑥 + 6) 3𝑥2 + 6𝑥 + 7
10.
(𝑥 2 + 9)2
11. 12. −
(𝑥 + 4)2 (3𝑥2 − 7)2

You should have found the following structures:


0(2𝑥 − 1) − 1(2) 3𝑥 2 (𝑥2 − 4) − 𝑥 3 (2𝑥) 1(𝑥 − 6) − (𝑥 + 4)1
13. 14. 15.
(2𝑥 − 1)2 (𝑥2 − 4)2 (𝑥 − 6)2
2(4𝑥 − 3) − (2𝑥 + 5)4 1(2𝑥2 − 8) − 𝑥(4𝑥) 1(𝑥2 ) − (𝑥 − 7)(2𝑥)
16. 17. 18.
(4𝑥 − 3)2 (2𝑥2 − 8)2 𝑥4
(2𝑥 + 4)(𝑥 + 3) − (𝑥 2 + 4𝑥 − 1)1 (2𝑥 − 9)(2𝑥 + 5) − (𝑥 2 − 9𝑥 + 11)2 3(𝑥2 + 12) − (3𝑥 − 1)(2𝑥)
19. (𝑥 + 3)2
20. (2𝑥 + 5)2
21.
(𝑥2 + 12)2
6(𝑥 2 − 𝑥 − 3) − (6𝑥 + 7)(2𝑥 − 1) (3𝑥 2 + 1)(𝑥 2 − 𝑥 − 1) − (𝑥 3 + 𝑥)(2𝑥 − 1) (10𝑥 − 2)(3𝑥 + 1) − (5𝑥 2 − 2𝑥)3
22. (𝑥 2 − 𝑥 + 3)2
23. (𝑥 2 − 𝑥 − 1)2
24. (3𝑥 + 1)2

The derivatives are:


𝑥+2 2(8𝑥 − 17)(2𝑥 + 7)2 21𝑥 − 31
25. 3 26. 27. −
(𝑥 + 1)2 (4𝑥 − 1)2 (7𝑥 + 3)5

3(4𝑥 + 13)(3𝑥 − 4)4 2𝑥 + 9 4𝑥 − 9


28. 29. 30. −
(2𝑥 + 1)4 2√(𝑥 + 1)3 2√𝑥 − 1(4𝑥 + 1)2
𝑥2 + 8𝑥 + 2 2(𝑥 + 2) 2(𝑥 − 3)(𝑥 + 3)3
31. − 32. 3
33.
√𝑥2 + 1(𝑥 − 8)3 3 √𝑥 4 𝑥3

The derivatives are:


𝑑𝑦 𝑥 + 4√𝑥 − 3 𝑑𝑓 2(𝑝 − 1) 𝑑𝑏 5(𝑤 2 − 1)
34. = 35. =− 3 36. =− 2
𝑑𝑥 2√𝑥(√𝑥 + 2)2 𝑑𝑝 3 √𝑝(2𝑝 + 1)2 𝑑𝑤
3𝑤 3 (𝑤2 + 5)2
𝑑𝑚 6ℎ2 𝑑𝑔 21𝑡 4 + 224𝑡 3 − 11 𝑑𝑒 57(4𝑦 + 3)2
37. = 3 38. = 39. =−
𝑑ℎ (ℎ + 1)2 𝑑𝑡 (𝑡 + 8)2 𝑑𝑦 (5𝑦 − 1)4
𝑑𝑘 8𝑛2 + 32𝑛 − 21 𝑑𝑟 3𝑣 − 32 𝑑𝑧 4𝑎 + 107
40. = 41. =− 42. = 7
𝑑𝑛 (𝑛 + 2)2 𝑑𝑣 2√(𝑣 + 1)7 𝑑𝑎
4(𝑎 + 5)4

The equations of the tangents (in gradient-intercept form) are:


43. 𝑦 = −4𝑥 + 13 44. 𝑦 = −11𝑥 + 15 45. 𝑦 = −2𝑥 + 9
3𝑥 1
46. 𝑦= + 47. 𝑦 = −16𝑥 + 37 48. 𝑦 = 13𝑥 − 19
4 4

http://www.CrystalClearMaths.com © Graeme Henderson (2015) ~ Free Use Permitted


~ Page 12 ~

You might also like